Analytic atheism in a low-religiosity culture: Examining the relationship between analytic thinking and religious belief in Germany. (August 2021) - Weiss, Alexa; Dorrough, Angela R.; Schmitz, Luisa
Abstract: Previous studies report a negative correlation between analytic thinking, typically assessed with the Cognitive Reflection Test (CRT), and religious belief. Recent research, however, revealed considerable cross-cultural divergence, suggesting weaker or absent effects in less religious countries. The present research investigated the relationship between analytic thinking and religious belief in three heterogeneous German-speaking samples ( N = 3063). In two preregistered re-analyses of existing data sets, analytic thinking as measured with the original CRT and an extended version emerged as a weak, but significant negative predictor of religious belief. However, when controlling for different measures of cognitive ability, this relationship held in some, but not all analyses. Cognitive ability consistently emerged as an independent predictor of (lower) religious belief. A third study closely following prior methodology again found the negative predictive effect of analytic thinking on established and extended measures of religious belief. Taken together, while replicating the relationship between analytic thinking and religious belief in a culture with low levels of religiosity, the present studies provide mixed evidence with respect to the specificity of this effect to an analytic cognitive style. We discuss the implications of these findings for the notion of analytic atheism. Highlights: Three studies investigate analytic atheism in Germany as a low-religiosity culture. We analyze data from two existing heterogeneous data sets and an original study. Analytic thinking consistently negatively predicted religious belief. This relationship was generally weak, but also depended on the measures used. Only in some analyses, it was robust to controlling for cognitive ability.